Crossing borders: A systematic review with quantitative analysis of genetic mutations of carcinomas of the biliary tract. (August 2019) - Roos, E.; Soer, E.C.; Klompmaker, S.; Meijer, L.L.; Besselink, M.G.; Giovannetti, E.; Heger, M.; Kazemier, G.; Klümpen, H.J.; Takkenberg, R.B.; Wilmink, H.; Würdinger, T.; et al.
Graphical abstract: Highlights: First systematic review to assess the mutational spectrum of biliary tract cancer. The different anatomical subtypes of biliary tract cancer show unique mutations. Extrahepatic cholangiocarcinoma shows mutations in APC, GNAS and TGFBR2. Mutations in IDH1, IDH2 and FGFR nearly exclusive to intrahepatic cholangiocarcinoma. Frequent mutations in gall bladder carcinoma are in PFKFB3, PLXN2 and PGAP1. Abstract: Biliary tract carcinoma (BTC) comprises gallbladder and intra-/extrahepatic cholangiocarcinoma (GBC, ICC, EHC), which are currently classified by anatomical origin. Better understanding of the mutational profile of BTCs might refine classification and improve treatment. We performed a systematic review of studies reporting on mutational profiling of BTC. We included articles reporting on whole-exome/whole-genome-sequencing (WES/WGS) and targeted sequencing (TS) of BTC, published between 2000-2017. Pooled mutation proportions were calculated, stratified by anatomical region and sequencing technique. A total of 25 studies with 1806 patients were included. Overall, TP53 was the most commonly mutated gene in BTC. GBC was associated with mutations in PFKFB3, PLXN2 and PGAP1. Mutations in IDH1, IDH2 and FGFR fusions almost exclusively occurred in ICC patients. Mutations in APC, GNAS and TGFBR2 occurred exclusively in EHC patients. In conclusion, subtypes of BTCs exhibit minor differences in mutational profile, which is likely influenced by the cell of origin.